Humanizing Cities as a Tool to Enhance Community Participation (Journal of Planner and Development, 2025)
This research investigates the concept of humanizing cities as a key approach to fostering community engagement and enhancing the quality of life in urban settings, with Bismayah City in Iraq serving as a case research. The research addresses a core issue: the deficiency in social interaction and the lack of integration between infrastructure and community activities. It posits that applying the principles of humanizing cities can promote social cohesion and advance sustainable development.The study employed a comprehensive analytical methodology, including a review of theoretical literature, field data analysis, and comparisons with global experiences. It tackled challenges such as the shortage of green spaces, limited reliance on renewable energy sources, and insufficient integration between public transportation and infrastructure.The findings highlighted the importance of developing public spaces, promoting cultural activities, and implementing sustainable environmental solutions.The research provides practical recommendations, including activating public participation in decision-making, enhancing the sustainability of infrastructure, and improving the integration of various urban planning components. It provides a theoretical and practical framework that can be applied to similar projects in local and international contexts.